Materials - Riley, Peter D.; Moller, Ray (London : Franklin Watts, 2008)
An introduction to various types of materials and their different properties.
First published: London : F. Watts, 2001.
Includes index.
4.6
K-3.
K-3
Keywords: Materials -- Juvenile literature; Materials; Materials